Physical properties, nutritional composition, and antioxidant profiles of five varieties of pumpkin (Cucurbita moschata) seeds - NURRAHMAN NURRAHMAN; AGUS SUYANTO; RAHAYU ASTUTI; YUNIKE KUSUMA DEWI; NUR AMALIA (Asian Journal of Agriculture, 2026)
Abstract. Nurrahman, Suyanto A, Astuti R, Dewi YK, Amalia N. 2026. Physical properties, nutritional composition, and antioxidant profiles of five varieties of pumpkin (Cucurbita moschata) seeds. Asian J Agric 10 (1): g100132. https://doi.org/10.13057/asianjagric/g100132. Pumpkin (Cucurbita moschata) seeds, in terms of their chemical and nutritional components, have potential as a functional food. The bioactive components contained in pumpkin seeds include carotenoids, tocopherols, antioxidants, and sterols. Pumpkin seed is also rich in bioactive compounds, such as phytosterols, which have antioxidant activity and potential for pharmacological research. The aim of this research is to determine the physical properties, nutritional composition, and antioxidant profiles of five varieties of pumpkin seeds. The research was conducted on five varieties of pumpkin; the pumpkins were cut in half and the seeds were removed. Then, the weight and volume of the seeds were measured. After that, the tested composition covered levels of proximate, fiber, fatty acids, amino acids, β-carotene, total phenols, antioxidant activity, and vitamins C and E. The data obtained were analyzed using the ANOVA method, and the LSD method was used to see the differences between each variety. Research results showed that the five varieties of pumpkin seeds had physical, compositional, nutritional, and antioxidant characteristics, as well as amino acids, that vary. The most common amino acids from the various varieties were glutamic acid, arginine, and aspartic acid. The seeds of Kabocha pumpkin had a composition of proximate, nutrients, antioxidants, and amino acids that are higher compared to other pumpkin seeds varieties. Meanwhile, the highest fatty acids were in the Ketan variety. Different varieties of pumpkin seeds had different physical and chemical characteristics.